Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

From agriculture back to tropical rainforest: When does ecological succession stabilize hot and dry extremes? - Felicity L. Newell; Edith Villa-Galaviz; Constance J. Tremlett; Sebastián Escobar; Adriana Argoti; Nicole Büttner; Julio Carvajal; María F. Checa; Katrin Krauth; Gustavo Pazmiño-Otamendi; Karen M. Pedersen; Bryan Tamayo; et al. (Agricultural and Forest Meteorology, 2026)

Long term rebound and transport of perfluorinated sulfonic acids (PFSAs) in the vadose zone following flushing - Charles E. Schaefer; Graig M. Lavorgna; David R. Lippincott; Shilai Hao; J. Conrad Pritchard; Christopher P. Higgins (Journal of Contaminant Hydrology, 2026)

P19-20 A Multi-Substrate Approach for Simultaneous Assessment of CYP Enzymatic Activities in various In vitro Hepatic Models - P. El Azzi; K. Maunand; T. Heckel; C. Dahyot; J. Hemon; C. Touma; P. Daligaux; M. Pinaud; I. Ouhssain; E. Richard; E. Schaefer (Toxicology Letters, 2025)

P19-03 The pyrrolizidine alkaloid lasiocarpine impairs cell cycle progression in vitro - S. Hessel-Pras; M. Beckschulte; A. Peters; A. Stahl; M. Templin; H. Sprenger; L. Boehmert; J.-H. Kuepper; B. Sachse; B. Schaefer (Toxicology Letters, 2025)

HESI GTTC ring trial: Concordance between Ames and rodent carcinogenicity outcomes for N-nitrosamines (NAs) with rat and hamster metabolic conditions - Joel Bercu; Alejandra Trejo-Martin; Connie Chen; Maik Schuler; Jennifer Cheung; Tetyana Cheairs; Anthony M. Lynch; Dean Thomas; Andreas Czich; Aisar Atrakchi; Timothy J. McGovern; Robert H. Heflich; et al. (Regulatory Toxicology and Pharmacology, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Geographic and Biological Drivers Shape Anthropogenic Extinctions in the Macaronesian Vascular Flora - Raúl Orihuela‐Rivero; Javier Morente‐López; J. Alfredo Reyes‐Betancort; Hanno Schaefer; Alfredo Valido; Miguel Menezes de Sequeira; Maria M. Romeiras; Carlos A. Góis‐Marques; Marcos Salas‐Pascual; Alain Vanderpoorten; José María Fernández‐Palacios; Jairo Patiño (Global Change Biology, 2025)
Whether species extinctions have accelerated during the Anthropocene and the extent to which certain species are more susceptible to extinction due to their ecological preferences and intrinsic biological traits are among the most pressing questions in conservation biology. Assessing extinction rates is, however, challenging, as best exemplified by the phenomenon of ‘ dark extinctions ’: the loss of species that disappear before they are even formally described. These issues are particularly problematic in oceanic islands, where species exhibit high rates of endemism and unique biological traits but are also among the most vulnerable to extinction. Here, we document plant species extinctions since Linnaeus' Species Plantarum in Macaronesia, a biogeographic region comprised of five hyperdiverse oceanic archipelagos, and identify the key drivers behind these extinctions. We compiled 168 records covering 126 taxa, identifying 13 global and 155 local extinction events. Significantly higher extinction rates were observed compared to the expected global background rate. We uncovered differentiated extinction patterns along altitudinal gradients, highlighting a recent coastal hotspot linked to socioeconomic changes in Macaronesian archipelagos from the 1960s onwards. Key factors influencing extinction patterns include island age, elevation, introduced herbivorous mammals, and human population size. Trait‐based analyses across the floras of the Azores and Canary Islands revealed that endemicity, pollination by vertebrates, nitrogen‐fixing capacity, woodiness, and zoochory consistently tended to increase extinction risk. Our findings emphasize the critical role of geography and biological traits, alongside anthropogenic impacts, in shaping extinction dynamics on oceanic islands. Enhancing our knowledge of life‐history traits within island floras is crucial for accurately predicting and mitigating future extinction risks, underscoring the urgent need for comprehensive biodiversity assessments in island ecosystems.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Serum per- and polyfluoroalkyl substance concentrations and longitudinal change in post-infection and post-vaccination SARS-CoV-2 antibodies - James Hollister; Alberto J. Caban-Martinez; Katherine D. Ellingson; Shawn Beitel; Ashley L. Fowlkes; Karen Lutrick; Harmony L. Tyner; Allison L. Naleway; Sarang K. Yoon; Manjusha Gaglani; Danielle Hunt; Jennifer Meece; et al. (Environmental Research, 2023)

Olfactory cues of risk and visual cues of safety interact with sympatry and phylogeny in shaping behavioral responses by littoral fishes - Brian D. Wisenden; Abygail A. Andebrhan; Cody M. Anderson; Jacob M. Angus; Ian C. Coffman; Madelyn E. Cloutier; Quintin H. Dahl; Alexander D. Doebler; Lily G. Erickson; Jenna E. McKay; Jessica I. Nguyen; Evan T. Nickchen; et al. (Behavioral Ecology and Sociobiology, 2023)

Assessing variants of uncertain significance implicated in hearing loss using a comprehensive deafness proteome - Mallory R. Tollefson; Rose A. Gogal; A. Monique Weaver; Amanda M. Schaefer; Robert J. Marini; Hela Azaiez; Diana L. Kolbe; Donghong Wang; Amy E. Weaver; Thomas L. Casavant; Terry A. Braun; Richard J. H. Smith; et al. (Human Genetics, 2023)
Hearing loss is the leading sensory deficit, affecting ~ 5% of the population. It exhibits remarkable heterogeneity across 223 genes with 6328 pathogenic missense variants, making deafness-specific expertise a prerequisite for ascribing phenotypic consequences to genetic variants. Deafness-implicated variants are curated in the Deafness Variation Database (DVD) after classification by a genetic hearing loss expert panel and thorough informatics pipeline. However, seventy percent of the 128,167 missense variants in the DVD are “variants of uncertain significance” (VUS) due to insufficient evidence for classification. Here, we use the deep learning protein prediction algorithm, AlphaFold2, to curate structures for all DVD genes. We refine these structures with global optimization and the AMOEBA force field and use DDGun3D to predict folding free energy differences (∆∆G Fold ) for all DVD missense variants. We find that 5772 VUSs have a large, destabilizing ∆∆G Fold that is consistent with pathogenic variants. When also filtered for CADD scores (> 25.7), we determine 3456 VUSs are likely pathogenic at a probability of 99.0%. Of the 224 genes in the DVD, 166 genes (74%) exhibit one or more missense variants predicted to cause a pathogenic change in protein folding stability. The VUSs prioritized here affect 119 patients (~ 3% of cases) sequenced by the OtoSCOPE targeted panel. Approximately half of these patients previously received an inconclusive report, and reclassification of these VUSs as pathogenic provides a new genetic diagnosis for six patients.

Facilitation of non-indigenous ascidian by marine eco-engineering interventions at an urban site - Nina Schaefer; Francisco Sedano; Melanie J. Bishop; Kate Dunn; M. Hank Haeusler; K. Daniel Yu; Yannis Zavoleas; Katherine A. Dafforn (Biofouling, 2023)

Detection of numerous phycotoxins in young bull sharks (Carcharhinus leucas) collected from an estuary of national significance - Michelle L. Edwards; Adam M. Schaefer; Malcolm McFarland; Spencer Fire; Christopher R. Perkins; Matthew J. Ajemian (Science of The Total Environment, 2023)

Predicting COVID-19 cases using SARS-CoV-2 RNA in air, surface swab and wastewater samples - Helena M. Solo-Gabriele; Shelja Kumar; Samantha Abelson; Johnathon Penso; Julio Contreras; Kristina M. Babler; Mark E. Sharkey; Alejandro M.A. Mantero; Walter E. Lamar; John J. Tallon; Erin Kobetz; Natasha Schaefer Solle; et al. (Science of The Total Environment, 2023)

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Elasmobranch Community Dynamics in Florida’s Southern Indian River Lagoon - Grace Roskar; Michael P. McCallister; Adam M. Schaefer; Matthew J. Ajemian (Estuaries and Coasts, 2021)

Heatwave‐induced synchrony within forage fish portfolio disrupts energy flow to top pelagic predators - Mayumi L. Arimitsu; John F. Piatt; Scott Hatch; Robert M. Suryan; Sonia Batten; Mary Anne Bishop; Rob W. Campbell; Heather Coletti; Dan Cushing; Kristen Gorman; Russell R. Hopcroft; Kathy J. Kuletz; et al. (Global Change Biology, 2021)
During the Pacific marine heatwave of 2014–2016, abundance and quality of several key forage fish species in the Gulf of Alaska were simultaneously reduced throughout the system. Capelin ( Mallotus catervarius ), sand lance ( Ammodytes personatus ), and herring ( Clupea pallasii ) populations were at historically low levels, and within this community abrupt declines in portfolio effects identify trophic instability at the onset of the heatwave. Although compensatory changes in age structure, size, growth or energy content of forage fish were observed to varying degrees among all these forage fish, none were able to fully mitigate adverse impacts of the heatwave, which likely included both top‐down and bottom‐up forcing. Notably, changes to the demographic structure of forage fish suggested size‐selective removals typical of top‐down regulation. At the same time, changes in zooplankton communities may have driven bottom‐up regulation as copepod community structure shifted toward smaller, warm water species, and euphausiid biomass was reduced owing to the loss of cold‐water species. Mediated by these impacts on the forage fish community, an unprecedented disruption of the normal pelagic food web was signaled by higher trophic level disruptions during 2015–2016, when seabirds, marine mammals, and groundfish experienced shifts in distribution, mass mortalities, and reproductive failures. Unlike decadal‐scale variability underlying ecosystem regime shifts, the heatwave appeared to temporarily overwhelm the ability of the forage fish community to buffer against changes imposed by warm water anomalies, thereby eliminating any ecological advantages that may have accrued from having a suite of coexisting forage species with differing life‐history compensations.

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

A comparative analysis of genetic hearing loss phenotypes in European/American and Japanese populations - W. Daniel Walls; Hideaki Moteki; Taylor R. Thomas; Shin-ya Nishio; Hidekane Yoshimura; Yoichiro Iwasa; Kathy L. Frees; Carla J. Nishimura; Hela Azaiez; Kevin T. Booth; Robert J. Marini; Diana L. Kolbe; et al. (Human Genetics, 2020)

PDGF-BB regulates splitting angiogenesis in skeletal muscle by limiting VEGF-induced endothelial proliferation - R. Gianni-Barrera; A. Butschkau; A. Uccelli; A. Certelli; P. Valente; M. Bartolomeo; E. Groppa; M. G. Burger; R. Hlushchuk; M. Heberer; D. J. Schaefer; L. Gürke; et al. (Angiogenesis, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

A tuff cone erupted under frozen-bed ice (northern Victoria Land, Antarctica): linking glaciovolcanic and cosmogenic nuclide data for ice sheet reconstructions - J. L. Smellie; S. Rocchi; J. S. Johnson; G. Di Vincenzo; J. M. Schaefer (Bulletin of Volcanology, 2018)

Bait worms: a valuable and important fishery with implications for fisheries and conservation management - Gordon J Watson; Joanna M Murray; Martin Schaefer; Adam Bonner (Fish and Fisheries, 2017)
Bait is an integral part of coastal life, but is perceived as a low‐value resource as fisheries are data‐limited, locally focussed and largely unregulated even though the ecological impacts of collection are considerable. An empirical assessment of three UK‐based ragworm fisheries combined with an analysis of published literature has produced the first global assessment of polychaete bait fisheries. The five most expensive (retail price per kg) marine species sold on the global fisheries market are polychaetes ( Glycera dibranchiata , Diopatra aciculata , Nereis ( Alitta ) virens , Arenicola defodiens and Marphysa sanguinea ). We estimate that 1600 t of N. virens per annum (worth £52 million) are landed in the UK with approximately 121 000 tonnes of polychaetes collected globally valued at £5.9 billion. Using remote closed circuit television (CCTV) cameras to monitor collectors, activity at local sites is considerable with a mean of 3.14 collectors per tide (day and night) at one site and individuals digging for up to 3 h per tide, although intensity differed seasonally and between sites. Collectors removed on average 1.4 kg of N. virens per person per hour, walking a considerable distance across the intertidal sediment to reach areas that were usually already dug. The implications of these human activity and biomass removal levels are explored in the context of fisheries and conservation management. At local, regional and national scales, polychaete bait fisheries are highly valuable, extract significant biomass and have considerable impacts; therefore, they urgently require governance equivalent to other fisheries.

Ecology and evolution of plant diversity in the endangered campo rupestre: a neglected conservation priority - Fernando A. O. Silveira; Daniel Negreiros; Newton P. U. Barbosa; Elise Buisson; Flávio F. Carmo; Daniel W. Carstensen; Abel A. Conceição; Tatiana G. Cornelissen; Lívia Echternacht; G. Wilson Fernandes; Queila S. Garcia; Tadeu J. Guerra; et al. (Plant and Soil, 2016)

Diversity and bioprospection of fungal community present in oligotrophic soil of continental Antarctica - Valéria M. Godinho; Vívian N. Gonçalves; Iara F. Santiago; Hebert M. Figueredo; Gislaine A. Vitoreli; Carlos E. G. R. Schaefer; Emerson C. Barbosa; Jaquelline G. Oliveira; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; Silvane M. F. Murta; et al. (Extremophiles, 2015)

A test of the cosmogenic 3 He production rate in the south‐west Pacific (39°S) - SHAUN R. EAVES; GISELA WINCKLER; JOERG M. SCHAEFER; MARCUS J. VANDERGOES; BRENT V. ALLOWAY; ANDREW N. MACKINTOSH; DOUGAL B. TOWNSEND; MATTHEW T. RYAN; XUN LI (Journal of Quaternary Science, 2015)
Calculation of surface exposure ages, using in situ cosmogenic nuclides, requires accurate knowledge of local production rates. Here, we report the first attempt to calibrate cosmogenic 3 He production in the south‐west Pacific region. We present a new radiocarbon chronology that precisely dates the emplacement of the Murimotu Formation, a large debris avalanche deposit in central North Island, New Zealand (ca. 830 m asl; 39°S), which occurred 10.4–10.6 cal ka BP. Measurements of cosmogenic 3 He in pyroxene separated from large andesitic blocks exposed during this event yield a sea‐level high‐latitude production rate of 120 ± 12 atoms g −1 a −1 (‘Lm’ scaling). This is consistent with a recent global compilation, comprised predominantly of calibration sites located in the Northern Hemisphere. Thus, we conclude that the globally compiled cosmogenic 3 He production rate is valid in the south‐west Pacific. Using independent, proximal calibrations of cosmogenic isotopes 10 Be and 14 C from quartz in New Zealand, we derive cosmogenic 3 He/ 10 Be and 3 He/ 14 C production ratios of 32.2 ± 3.2 and 10.6 ± 1.6, respectively.

Statistical Comparison of Dissolution Profiles to Predict the Bioequivalence of Extended Release Formulations - J. D. Gomez-Mantilla; U. F. Schaefer; V. G. Casabo; T. Lehr; C. M. Lehr (The AAPS Journal, 2014)

Expert assessment of vulnerability of permafrost carbon to climate change - E. A. G. Schuur; B. W. Abbott; W. B. Bowden; V. Brovkin; P. Camill; J. G. Canadell; J. P. Chanton; F. S. Chapin; T. R. Christensen; P. Ciais; B. T. Crosby; C. I. Czimczik; et al. (Climatic Change, 2013)

Genetic isolation of wolverine (Gulo gulo) populations at the eastern periphery of their North American distribution - Joanna Zigouris; F. Neil Dawson; Jeff Bowman; Roxanne M. Gillett; James A. Schaefer; Christopher J. Kyle (Conservation Genetics, 2012)

Calibration of the in situ cosmogenic 14 C production rate in New Zealand's Southern Alps - Irene Schimmelpfennig; Joerg M. Schaefer; Brent M. Goehring; Nathaniel Lifton; Aaron E. Putnam; David J. A. Barrell (Journal of Quaternary Science, 2012)
In situ cosmogenic 14 C ( in situ 14 C) analysis from quartz‐bearing rocks is a novel isotopic tool useful for quantifying recent surface exposure histories (up to ∼25 ka). It is particularly powerful when combined with longer‐lived cosmogenic isotopes such as 10 Be. Recent advances in the extraction of in situ 14 C from quartz now permit the routine application of this method. However, only a few experiments to calibrate the production rate of in situ 14 C in quartz have been published to date. Here, we present a new in situ 14 C production rate estimate derived from a well‐dated debris flow deposit in the Southern Alps, New Zealand, previously used to calibrate 10 Be production rates. For example, based on a geomagnetic implementation of the Lal/Stone scaling scheme we derive a spallogenic production rate of 11.4 ± 0.9 atoms 14 C (g quartz) −1 a −1 and a 14 C/ 10 Be spallogenic production rate ratio of 3.0 ± 0.2. The results are comparable with production rates from previous calibrations in the northern hemisphere. Copyright © 2012 John Wiley & Sons, Ltd.

Putting biogeography’s cart back behind taxonomy’s horse: a response to Triantis et al. - Mark A. Carine; Katy Jones; Mónica Moura; M. Graciete Belo Maciel; Fred J. Rumsey; Hanno Schaefer (Journal of Biogeography, 2012)
In a recent paper, two of us discussed diversity patterns and diversification processes in the Azores flora. Triantis et al. (2012, Journal of Biogeography , 39, 1179–1184) challenged our hypothesis that palaeoclimatic differences had an effect on diversification rates and suggested that area, island age and isolation explain diversity patterns. They did not, however, fully address the results from our subsequent paper, in which we showed that diversity patterns evident from phylogeographic studies differ markedly from those suggested by checklists. Checklists are working hypotheses and we suggest that the discrepancies evident between molecular data and checklists may be indicative of deficiencies in our taxonomic understanding of the Azores flora. Patterns of molecular and morphological diversity need to be better understood, and the discrepancies between checklists and molecular data accounted for, before we can establish the relative importance of factors such as palaeoclimate, area, island age or isolation in generating endemic diversity patterns in the Azores flora.

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

A rebuttal to “Repeated measurements and pseudo‐replication in captive studies” - Todd Schmitt; Adam M. Schaefer; J. Lawrence Dunn (Marine Mammal Science, 2012)

Baseline, diurnal variations, and stress-induced changes of stress hormones in three captive beluga, Delphinapterus leucas - Todd L. Schmitt; David J. St. Aubin; Adam M. Schaefer; J. Lawrence Dunn (Marine Mammal Science, 2010)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Landscape genetics of California mule deer ( Odocoileus hemionus ): the roles of ecological and historical factors in generating differentiation - KATHERINE M. PEASE; ADAM H. FREEDMAN; JOHN P. POLLINGER; JOHN E. MCCORMACK; WOLFGANG BUERMANN; JEFF RODZEN; JIM BANKS; ERIN MEREDITH; VERNON C. BLEICH; ROBERT J. SCHAEFER; KEN JONES; ROBERT K. WAYNE (Molecular Ecology, 2009)
Landscape genetics is an emerging discipline that utilizes environmental and historical data to understand geographic patterns of genetic diversity. Niche modelling has added a new dimension to such efforts by allowing species–environmental associations to be projected into the past so that hypotheses about historical vicariance can be generated and tested independently with genetic data. However, previous approaches have primarily utilized DNA sequence data to test inferences about historical isolation and may have missed very recent episodes of environmentally mediated divergence. We type 15 microsatellite loci in California mule deer and identify five genetic groupings through a Structure analysis that are also well predicted by environmental data. We project the niches of these five deer ecotypes to the last glacial maximum (LGM) and show they overlap to a much greater extent than today, suggesting that vicariance associated with the LGM cannot explain the present‐day genetic patterns. Further, we analyse mitochondrial DNA (mtDNA) sequence trees to search for evidence of historical vicariance and find only two well‐supported clades. A coalescence‐based analysis of mtDNA data shows that the genetic divergence of the mule deer genetic clusters in California is recent and appears to be mediated by ecological factors. The importance of environmental factors in explaining the genetic diversity of California mule deer is unexpected given that they are highly mobile species and have a broad habitat distribution. Geographic differences in the timing of reproduction and peak vegetation as well as habitat choice reflecting natal origin may explain the persistence of genetic subdivision.

Soil and vegetation carbon stocks in Brazilian Western Amazonia: relationships and ecological implications for natural landscapes - C. E. G. R. Schaefer; E. F. do Amaral; B. A. F. de Mendonça; H. Oliveira; J. L. Lani; L. M. Costa; E. I. Fernandes Filho (Environmental Monitoring and Assessment, 2008)

On the relationship between hydrocarbon migration pathways and carbonate mound occurrence in the Porcupine Basin - J. Naeth; R. di Primio; B. Horsfield; R. G. Schaefer; B. M. Krooss (International Journal of Earth Sciences, 2007)

Occupancy of dopamine D1, D2 and serotonin2A receptors in schizophrenic patients treated with flupentixol in comparison with risperidone and haloperidol - M. Reimold; C. Solbach; S. Noda; J.-E. Schaefer; M. Bartels; M. Beneke; H.-J. Machulla; R. Bares; T. Glaser; H. Wormstall (Psychopharmacology, 2006)

Gait transition and oxygen consumption in swimming striped surfperch Embiotoca lateralis Agassiz - M. Cannas; J. Schaefer; P. Domenici; J. F. Steffensen (Journal of Fish Biology, 2006)
A flow‐through respirometer and swim tunnel was used to estimate the gait transition speed ( U p‐c ) of striped surfperch Embiotoca lateralis , a labriform swimmer, and to investigate metabolic costs associated with gait transition. The U p‐c was defined as the lowest speed at which fish decrease the use of pectoral fins significantly. While the tail was first recruited for manoeuvring at relatively low swimming speeds, the use of the tail at these low speeds [as low as 0·75 body (fork) lengths s −1 , L F s −1 ) was rare ( U p‐c , pectoral fin (PF) frequencies kept increasing when the tail was not used, while they did not when PF locomotion was aided by the tail. At these high speeds, the tail was employed for 40–50% of the time, either in addition to pectoral fins or during burst‐and‐coast mode. Oxygen consumption increased exponentially with swimming speeds up to gait transition, and then levelled off. Similarly, cost of transport ( C T ) decreased with increasing speed, and then levelled off near U p‐c . When speeds ≥ U p‐c are considered, C T is higher than the theoretical curve extrapolated for PF swimming, suggesting that PF swimming appears to be higher energetically less costly than undulatory swimming using the tail.

Analysis of mercuric reductase ( merA ) gene diversity in an anaerobic mercury‐contaminated sediment enrichment - Sinéad M. Ní Chadhain; Jeffra K. Schaefer; Sharron Crane; Gerben J. Zylstra; Tamar Barkay (Environmental Microbiology, 2006)
Summary The reduction of ionic mercury to elemental mercury by the mercuric reductase (MerA) enzyme plays an important role in the biogeochemical cycling of mercury in contaminated environments by partitioning mercury to the atmosphere. This activity, common in aerobic environments, has rarely been examined in anoxic sediments where production of highly toxic methylmercury occurs. Novel degenerate PCR primers were developed which span the known diversity of merA genes in Gram‐negative bacteria and amplify a 285 bp fragment at the 3′ end of merA . These primers were used to create a clone library and to analyse merA diversity in an anaerobic sediment enrichment collected from a mercury‐contaminated site in the Meadowlands, New Jersey. A total of 174 sequences were analysed, representing 71 merA phylotypes and four novel MerA clades. This first examination of merA diversity in anoxic environments suggests an untapped resource for novel merA sequences.

Biopharmaceutical Characterization of the Telomerase Inhibitor BRACO19 - S. Taetz; C. Baldes; T. E. Mürdter; E. Kleideiter; K. Piotrowska; U. Bock; E. Haltner-Ukomadu; J. Mueller; H. Huwer; U. F. Schaefer; U. Klotz; C.-M. Lehr (Pharmaceutical Research, 2006)

The progesterone derivative dydrogesterone down-regulates neurokinin 1 receptor expression on lymphocytes, induces a Th2 skew and exerts hypoalgesic effects in mice - Arif Suphi Orsal; Sandra Blois; Dominika Labuz; Eva M. J. Peters; Martin Schaefer; Petra C. Arck (Journal of Molecular Medicine, 2006)

Enhanced resistance to early blight in transgenic tomato lines expressing heterologous plant defense genes - Scott C. Schaefer; Ksenija Gasic; Bruno Cammue; Willem Broekaert; Els J. M. van Damme; Willy J. Peumans; Schuyler S. Korban (Planta, 2005)

Leukocyte adhesion in aorta and femoral artery in vivo is mediated by LFA-1 - R. Schramm; M. D. Menger; H. -J. Schaefers; H. Thorlacius (Inflammation Research, 2004)

Exploring the potential of life‐history key innovation: brook breeding in the radiation of the Malagasy treefrog genus Boophis - M. Vences; F. Andreone; F. Glaw; J. Kosuch; A. Meyer; H.‐C. Schaefer; M. Veith (Molecular Ecology, 2002)
The treefrog genus Boophis is one of the most species‐rich endemic amphibian groups of Madagascar. It consists of species specialized to breeding in brooks (48 species) and ponds (10 species). We reconstructed the phylogeny of Boophis using 16S ribosomal DNA sequences (558 bp) from 27 species. Brook‐breeders were monophyletic and probably derived from an ancestral pond‐breeding lineage. Pond‐breeders were paraphyletic. The disparity in diversification among pond‐breeders and brook‐breeders was notable among endemic Malagasy frogs, although it was not significant when considering Boophis alone. Sibling species which have different advertisement calls but are virtually indistinguishable by morphology were common among brook‐breeders; genetic divergence between these species was high (modal 8% total pairwise divergence). Substitution rates in brook‐breeding species were significantly higher than in pond‐breeders. Speciation of pond‐breeders may be hindered by their usually more synchronous reproduction and a higher vagility which enhances gene flow, while a higher potential of spatial segregation and speciation may exist along brooks.

Caribou movement as a correlated random walk - C. M. Bergman; J. A. Schaefer; S. N. Luttich (Oecologia, 2000)

Bioequivalence of Topical Dermatological Dosage Forms-Methods of Evaluation of Bioequivalence - Vinod P. Shah; Gordon L. Flynn; Avraham Yacobi; Howard I. Maibach; Charles Bon; Nicholas M. Fleischer; Thomas J. Franz; Stanley A. Kaplan; Jeff Kawamoto; Lawrence J. Lesko; Jean-Paul Marty; Lynn K. Pershing; et al. (Pharmaceutical Research, 1998)